Comparison of immune and health markers in intact and neonatally castrated male pigs. (5th October 2013) - Merlot, E.; Thomas, F.; Prunier, A.
Abstract : Stress and sex hormones are known to regulate immune function. Castration of male piglets is used to avoid boar taint in the meat, but its consequences on immunity and health of male pigs are poorly known. In this study, intact and neonatally surgically castrated male pigs (n=20 per group) were compared along puberty for some immune parameters and hormone receptor expression in lymphoid organs. Pigs were immunised with keyhole limpet haemocyanin (KLH) at 113 and 133 days of age. Blood lymphocyte numbers and proliferation, immunoglobulin titres, haptoglobin and hormone levels at 89, 119 and 152 days and the mRNA expression of androgen, α‐oestrogen, glucocorticoid and β2‐adrenergic receptors in liver, spleen and thymus at 160 days were assessed. Blood lymphocyte numbers were lower (at 119 and 152 days) and total IgG and haptoglobin concentrations were higher (at 152 days) in castrated than intact males. The concanavalin A and KLH proliferation responses and anti‐KLH IgG titres were not altered. At slaughter, intact pigs presented a heavier thymus and a lower hepatic expression of β2‐adrenergic receptor. In conclusion, the effects of neonatal castration were moderate. Other studies are needed to clarify the possible detrimental outcomes of castration on lymphocyte numbers and thymic growth.